Opportunities for adult learners through integrated e-learning - Nantha Kumar , Subramaniam (2011)
The distance learning environment has a major contribution to make to the educational requirements of the 21st century by encouraging the acceptance of lifelong learning (LLL). Keeping pace with changes in technology and meeting the increasing demands of the knowledge based economy requires a highly skilled and educated workforce. The solution would then have to be to foster educational opportunities which would invariably lead to continuing education through the concept of LLL. Avenues would then point to integrated elearning with its egalitarian environment of open access and greater opportunities for the learners particularly the adult learners. The integrated e-learning opportunities would be able to satisfy the students’ need for convenient offerings and at the same time maximize the use of online teaching technologies, facilities and resources reducing presence in a classroom environment. Arguably traditional classroom methods present an important presence in the teaching-learning process but the use of technology presents the challenges of the future. Technology has now integrated into higher education and this paper attempts to explore the opportunities and challenges that online learning in general and Open University Malaysia in particular face in implementing lifelong learning to cater to the adult learners. (Abstract by author)